An e-mail exchange analysis framework for project management support - Swacha, Jakub (Wspomaganie zarządzania projektami za pośrednictwem analizy poczty elektronicznej, 2011)
In the paper a new e-mail exchange analysis framework is proposed and described, aimed at supporting project management in both business and non-business organizations. The framework acquires data from IMAP servers and processes them to create reports on communication activity between project stakeholders in graphical and tabular forms. The reports can be useful in analyzing the internal communication structure of the project team, identifying the key project members responsible for communication with external parties, as well as discerning project members with over- or sub-average communication activity. The framework has been implemented in Python as open-source software
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2011, Nr 202, s. 88-96
Keywords: e-mail; project management; analysis framework